Consumer returns processing in a multi-period setting. (14th December 2022) - Ciftci, Kamil; Tanai, Yertai; Wilson, George R.
The modern business world dictates that managing product returns to be an invaluable component of a firm's overall business bottom line and supply chain strategy. In this paper, we propose a quantitative framework for a responsive reverse supply chain where a retailer processes the returns. Under a competitive full refund policy by the retailer and utilising price inversely influenced demand for a given period, we formulate a holistic profit maximisation model for the entire planning horizon. We derive closed form solutions for the optimal sales price and quantity of processed returns for a particular period and derive the effects of some key parameters on the decision variables. A primary result is that the average selling price is always lower with processing. Furthermore, the value captured from the processing of returns increases as the product becomes more expensive to acquire. Lastly, the value gained from processing additional returns is always declining for each additional period of delay, indicating the importance of adopting a responsive returns management process.